Circ_0065149 Alleviates Oxidized Low-Density Lipoprotein-Induced Apoptosis and Inflammation in Atherosclerosis by Targeting miR-330-5p - Li, Dan; Jin, Wen; Sun, Li; Wu, Jiawei; Hu, Hao; Ma, Likun (Frontiers in Genetics, 2021)
Background: Atherosclerosis is a risk factor for cardiovascular diseases. However, the roles of Circular RNAs (circRNAs) in atherosclerosis is unknown. Our study aimed to explore the effects of circ_0065149 in the pathogenesis of atherosclerosis. Methods: The expression of circ_0065149 ox-LDL-induced in human umbilical vein endothelial cells (HUVECs) was assessed by RT-PCR. Cell viability, lactate dehydrogenase leakage, apoptosis, invasion, and migration were assessed in HUVECs. Dual luciferase reporter system was carried out to determine the interaction between miR-330-5p and circ_0065149. Results: Our results showed that circ_0065149 was significantly lower in the ox-LDL-induced HUVECs. Overexpression of circ_0065149 promoted the cell viability and inhibited the apoptosis of ox-LDL-induced HUVECs. Overexpression of circ_0065149 also promoted the migration and invasion of ox-LDL-induced HUVECs. The expression of miR-330-5p was inhibited by overexpression of circ_0065149. Furthermore, circ_0065149 overexpression significantly inhibited the expressions of nuclear NF-κBp65, and suppressed the production of TNF-α, IL-6, and IL-1β in ox-LDL-induced HUVECs, which was rescued by the miR-330-5p mimic. Conclusion: These findings suggest that circ_0065149 plays an important role in the proliferation, apoptosis and inflammatory response of HUVECs via targeting miR-330-5p.